The Role of Knowledge Sharing in Linking Transformational Leadership with Innovative Work Behavior and Employee Performance in the Public Sector - Febrianti Indah Pratiwi; Heri Fathurahman (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of Transformational Leadership on Innovative Work Behavior and Employee Performance through the mediating role of Knowledge Sharing among employees of the Ministry of State Secretariat. Research Methodology: A quantitative approach was employed using data collected from 200 employees through a structured questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: Transformational Leadership positively and significantly affects Knowledge Sharing, Innovative Work Behavior, and Employee Performance. Knowledge Sharing also positively influences Innovative Work Behavior and Employee Performance and significantly mediates the relationship between Transformational Leadership and both outcomes. Among all predictors, Knowledge Sharing exhibits the strongest effect on employee innovation and performance. Conclusions: Knowledge Sharing emerged as the strongest predictor of employee innovation and performance and served as a significant mediator between Transformational Leadership and both outcomes. This finding underscores the importance of fostering collaborative learning and knowledge exchange to maximize the effectiveness of transformational leadership. Limitations: This research focused on a single public institution and used a cross-sectional design. Contributions: This study contributes to the organizational behavior and public sector management literature by providing evidence of the mediating role of Knowledge Sharing in linking Transformational Leadership with employee innovation and performance within a government institution undergoing bureaucratic reform.